Hydromechanical behavior of radially multilayered cylinders under time-varying loads. Issue 4 (21st April 2019) - Zhou, Feng; Song, Zhu; Lin, Cheng
ABSTRACT: Geotechnical strata are often treated as horizontally homogeneous for hydromechanical analysis due to the vertical deposition of geological layers; however, such a treatment becomes no longer valid when vertical drilling or construction causes the localized disturbance of subsurface, which would result in radial heterogeneity of geomaterials. This paper presents a poroelastic solution for the saturated multilayered cylinder where multilayer is used to represent radial heterogeneity. After the application of Laplace transform, the governing equations in cylindrical coordinates are derived to obtain the stiffness matrix between stresses, displacements, and pore water pressure. The global matrix is assembled by the boundary conditions and the compatibility of interfaces between adjacent layers. Under time-dependent horizontal compression loads, a parametric study is performed for a cylinder comprised of two layers with distinct properties, and the results show that the load frequency and radial heterogeneity play a significant role in hydromechanical behavior of geomaterials: (1) the time-varying loading can induce a negative pore pressure, and the influence of cyclic loading with a high frequency is limited near the outer surface; (2) the radial heterogeneity due to permeability and compressibility affects the development of pore pressure.